How do health workers perceive and practice monitoring and evaluation of malaria control interventions in South-east Nigeria? - Mbachu, Chinyere O (BioMed Central, 2013)
BACKGROUND: The Anambra state Malaria Control Booster Project (ANMCBP) depends on an effective monitoring and evaluation (M&E) system to continuously improve the implementation of the malaria control interventions. However, it is not clear how the health workers that are expected to be the fulcrum of the malaria M&E perceive and practise M&E. The study was carried out to determine the knowledge, perception, and practice of Malaria M&E among selected health staff, and to identify related socio-demographic factors, including cadre of staff. METHODS: A semi-structured questionnaire and an observation checklist were used to collect information from selected health workers in public primary health centres in all 21 local government areas of the State. Multistage sampling technique was used in selection of respondents. The questionnaire explored knowledge, perception and practice of malaria M&E from 213 health workers. The observation checklist was used to record the actual practice of malaria M&E as observed by trained supervisors. RESULTS: Over 80% of health workers interviewed were able to correctly identify the malaria M&E forms; 25.4% knew the basis for categorizing Artemisinin-based combination therapy (ACT) into ACT1 - ACT4; 97.6% of the respondents felt there was need to keep proper records to have information available and 7.5% of them kept records because they were asked to do so. Over 90% of respondents reported correct practice of M&E, but on verification of actual practice, 55.6% of the respondents had at least one wrongly filled form, and half of these had none of their forms properly filled; about 68.4% of respondents had met specified timeline for data transmission. Differences observed in knowledge, perception and practice of M&E across age categories and cadres were only significant in ability to identify malaria M&E forms; diagnosis of malaria based on blood film microscopy result; perception of how age should be recorded; and reported practice of keeping data till they are requested. Among lower cadre of staff, gaps still exist in knowledge, perception and practice of malaria M&E. CONCLUSIONS: Gaps still exist in health workers’ understanding of malaria data management, perception of efficient data transmission and observed practice of malaria M&E.